Teacher Education Students’ Implicit Racial Attitudes and Interpersonal Attribution of Racialized Student Behavior - Lorenzetti, Nicole L.; Johnson, Helen (Journal of Contemporary Issues in Education)

(untitled) (University of Alberta, 2023)
Teachers have been shown to hold lower behavioral expectations for Black students than for their White peers, and the mechanism underlying this may be teachers’ implicit attitudes about their Black students based on causal attributions. This study examined this connection, predicting that teacher education students (TES) who scored higher on the racial implicit bias test would attribute internal causality and controllability to explain challenging behaviors in the classroom more frequently for Black students than for White students. 233 teacher education students completed the racial bias section of the Implicit Assessment Test and a set of questions assessing causal attribution based on four vignettes depicting student misbehaviors in a classroom setting. We found that regardless of implicit bias, TES were more likely to believe that Black students had an internal locus of causality and controllability than their White counterparts when presented with similar instances of challenging behavior. These results support the need for teacher preparation programs to address how these internal beliefs of teacher education students affect what they learn about managing their expectations around students’ behavioral regulation and to what they attribute these behaviors.